Benefits of Avène thermal hydrotherapy in chronic skin diseases and dermatological conditions: an overview. (1st September 2020) - Nocera, T.; Jean‐Decoster, C.; Georgescu, V.; Guerrero, D.
Abstract: The beneficial effects of Avène Thermal Spring Water (TSW), a low mineral content spring water, on chronic skin diseases have been recognized for more than two centuries. This article provides a brief overview of efficacy and tolerance data for Avène TSW from clinical studies conducted at the Avène Hydrotherapy Center in patients with chronic inflammatory skin diseases or temporary skin injuries. Avène TSW hydrotherapy is effective as adjuvant management for chronic skin diseases and dermatological conditions, relieving subjective and physical symptoms with excellent tolerance.